PENINGKATAN PENDAPATAN PEREMPUAN MELALUI PENGEMBANGAN USAHA EKONOMI KREATIF KERAJINAN BORDIR ACEH (Kajian Di Kecamatan Montasik, Kabupaten Aceh Besar) - Filia Hanum; Juwita Juwita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to see how the development of Aceh's embroidery creative economy in increasing the income of women who are members of several groups of Acehnese embroidery craftsmen in Dayah Daboh village and Weu Krueng village, Montasik district, Aceh Besar district. The research was conducted using a qualitative descriptive method. Data collection techniques are observation, interviews and documentation. Based on the results of the analysis, it is known that the development and sustainability of the creative economy of the embroidery industry in the two villages has looked good and can increase the income of women craftsmen. Of the 150 women who are members of several artisan groups as informants, it was found that 100% of them stated that their income had increased rapidly from year to year. In addition, the income from the production of the embroidery industry of these craftsmen can meet their daily needs. With the development of the embroidery craft as one of the creative economic efforts, it can increase the income of women craftsmen so that they can help their family life and can help family income in addition to the income earned by their husbands.